Azacitidine regulates DNA methylation of GADD45γ in myelodysplastic syndromes. Issue 2 (20th October 2020) - Yang, Yanli; Li, Jun; Geng, Yinghua; Liu, Lin; Li, Dianming
Abstract: Background: Myelodysplastic syndrome (MDS) is a heterogeneous clonal disease originated from hematopoietic stem cells. Epigenetic studies had demonstrated that DNA methylation and histone acetylation were abnormal in MDS. Azacitidine is an effective drug in the treatment of demethylation. Methods: RT‐PCR was performed to determine GADD45γ in 15 MDS clinical samples. Myelodysplastic syndrome cell lines SKM‐1 and HS‐5 were transfected with GADD45γ eukaryotic expression vector and/or GADD45γ shRNA interference plasmid, and treated with azacitidine. Proliferation and apoptosis were examined by CCK‐8 and Western blot analysis to confirm the function role of GADD45γ and azacitidine. The methylation level of GADD45γ gene was detected by bisulfite conversion and PCR. Results: This study found that GADD45γ gene was down‐expressed in MDS patients' bone marrow and MDS cell lines, and the down‐regulation of GADD45γ in MDS could inhibit MDS cell apoptosis and promote proliferation. Azacitidine, a demethylation drug, could restore the expression of GADD45γ in MDS cells and inhibit the proliferation of MDS cells by inducing apoptosis, which was related to prognosis and transformation. Conclusion: This study indicated that GADD45γ was expected to become a new target of MDS‐targeted therapy. The findings of this study provided a new direction for the research and development of new MDS clinical drugs, and gave a new idea for the development of MDS demethylation drug to realize precise treatment. Abstract : Azacitidine Induce MDS cell apoptosis.